A modified projection algorithm for constrained equilibrium problems. (2nd December 2017) - Santos, P. S. M.; Scheimberg, S.
Abstract : Based on the constrained variational inequality problem considered by Censor, Gibali and Reich (Numerical Algorithms, 2012), we propose, the constrained equilibrium problem (CEP), which consists in finding a point in the intersection of two nonempty, closed and convex subsets of an Euclidean space, C and D, such that is a solution of an equilibrium problem on C . In this work, an algorithm using projections is proposed to solve (CEP). Convergence properties of the algorithm are established under mild assumptions. Some numerical results are reported.